The influence of the built environment on outcomes from a “walking school bus study”: a cross-sectional analysis using geographical information systems - Oreskovic, Nicolas M. (Geospat Health, 2014)
Active commuting to school increases children’s daily physical activity. The built environment is associated with children’s physical activity levels in cross-sectional studies. This study examined the role of the built environment on the outcomes of a “walking school bus” study. Geographical information systems was used to map out and compare the built environments around schools participating in a pilot walking school bus randomised controlled trial, as well as along school routes. Multi-level modelling was used to determine the built environment attributes associated with the outcomes of active commuting to school and accelerometer-determined moderate-to-vigorous physical activity (MPVA). There were no differences in the surrounding built environments of control (n = 4) and intervention (n = 4) schools participating in the walking school bus study. Among school walking routes, park space was inversely associated with active commuting to school (β = −0.008, SE = 0.004, P = 0.03), while mixed-land use was positively associated with daily MPVA (β = 60.0, SE = 24.3, P = 0.02). There was effect modification such that high traffic volume and high street connectivity were associated with greater moderate-to-vigorous physical activity. The results of this study suggest that the built environment may play a role in active school commuting outcomes and daily physical activity.